Immersive storm surge flooding: Scale and risk perception in virtual reality. (April 2022) - Simpson, Mark; Padilla, Lace; Keller, Klaus; Klippel, Alexander
Abstract: Immersive virtual reality (iVR) can enable users to experience phenomena at real-world scale. This attribute may be useful for communicating the risks of many natural hazards. Storm-surge is a flood hazard whose risk has proven challenging to communicate through traditional means, such as maps. When it comes to storm-surge flooding, iVR experiences have shown promise in increasing awareness of their danger. However, it is currently unclear whether iVR enhances risk perception over standard display methods, and how such experiences affect the interpretation of map products. To address these questions, we ran a between-participants experiment comparing the impact of display type (desktop versus iVR) on risk perception and spatial learning, using a custom-developed immersive simulation of storm-surge flooding. We measured perceived risk by having participants rate damage on a series of hypothetical storm-surge maps and making evacuation decisions in response to notional flooding. To understand if more accurately sized iVR representation led to better comprehension of flood heights, we measured participants' ability to point to flood heights in a real environment. We found that iVR increases map damage-ratings and real-world height estimation accuracy, but that iVR leads participants to report that they would evacuate (and evacuate others) at higher water levels, indicating a disconnect between their understanding of environmental and bodily danger. We found that both desktop and iVR experiences aid map interpretation while iVR improves recall of flood heights in the real world. These results provide an avenue towards greater understanding of how iVR may be used for hazard-risk communication and conveying spatial information from immersive environments. Highlights: We ran an evaluation of an immersive virtual reality (VR) experience of a storm-surge flood hazard. Impact of VR on hazard risk perception depends on how it is measured. Virtual flooding led to reduced risk perception for bodily harm, but higher for environmental harm. Spatial knowledge (scale) developed in virtual environment transferred to real environment.